Climate Smart Agriculture: a primer of local government officials in the Philippines (Khmer Version) - Gonsalves, Julian Francis; Vidallo, Rene R.; Monville-Oro, Emilita; Barbon, Wilson John; Rosimo, Magnolia M.; Jordan, Jonna; Dalusag, Joanna B.; Romero, Joshua; Servano, Gonzalo S.; Baguilat, Irish; Rosales, Belina O; Narte, Julieta; et al. (2019)
The primer helps to identify and address important interactions, synergies and trade-offs between and among climate change, agriculture and food security. ‘Understanding Climate Change’ explains the definition of climate change, stressing on greenhouse gasses (GHGs) and their impacts on agriculture. Local partners of CCAFS, including local government units, media practitioners, and other stakeholders in the agriculture sector, are the primary audience of the primer. This version is translated in Khmer (the national language of Cambodia).